Pengaruh Product Quality Terhadap Customer Loyalty Melalui Digital Marketing Pada Produk Somethinc : Studi Pada Mahasiswa UNISMA - Fian Arifiona Faradila; Isymayati Ash Shiddiqy (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to find out how much Product Quality affects Customer Loyalty through Digital Marketing of Somethinc products (Case Study of students at the Islamic University of Malang). This research consists of one independent variable, namely Product Quality and one dependent variable, namely Customer Loyalty and Digital Marketing as intervening variables. The analysis method used is path analysis. The data collection method in this research was to use a questionnaire filled in by respondents, namely UNISMA students who bought and used Somehinc products. The research results obtained based on the Partial Test (t Test) showed: a) there is a significant influence of Product Quality on Digital Marketing, b) there is a significant influence of Product Quality on Customer Loyalty, c) there is a significant influence of Digital Marketing on Customer Loyalty.